Snow cover, freeze‐thaw, and the retention of nutrients in an oceanic mountain ecosystem. Issue 10 (29th October 2015) - Wipf, Sonja; Sommerkorn, Martin; Stutter, Marc I.; Wubs, E. R. Jasper; van der Wal, René
Abstract : As the climate warms, winters with less snow and therefore more soil freeze‐thaw cycles are likely to become more frequent in oceanic mountain areas. It is a concern that this might impair the soil's ability to store carbon and nutrients, and lead to increased leaching losses of dissolved C and nutrients and subsequent changes in nutrient cycling and ecosystem productivity. Through a combination of laboratory and field experiments, we studied short‐term effects of changing winter conditions on carbon and nutrient leaching from two plant‐soil systems with contrasting snow conditions (shallow/intermittent vs. deep/persistent snow). In the laboratory we exposed cores (soil and vegetation) from sites with either intermittent or persistent winter snow cover to five different freeze‐thaw scenarios of realistic frequency and duration. Additionally, we set up a transplant experiment at our field site by reciprocally transplanting soil‐plant monoliths between sites with intermittent and persistent snow. Together, the field and laboratory experiments aimed to assess how carbon and nutrient leaching was affected by both historical snow conditions and short‐term (through freeze‐thaw scenarios and transplantation) changes in snow cover and thermal conditions. Both a greater number of freeze‐thaw cycles and longer duration of sub‐zero temperatures increased carbon and nutrient leaching from incubated soil cores. Cores from sites with persistent snow generally had lower nutrient losses under control conditions, but greater losses following induced freeze‐thaw cycles than cores from intermittent snow sites. The character of the leached dissolved organic carbon (DOC) suggested fresh organic material, such as live plant roots or microbes, as the source of carbon and nutrients. Nutrient losses from the plant‐soil systems in the field were greater at sites with persistent winter snow due to greater volumes of percolating water in spring. This suggests that increasingly severe and frequent soil freeze‐thaw events in oceanic mountain ecosystems can enhance the mobilization of C, N and P in labile forms but, in the absence of water fluxes, these nutrients would remain available for in‐situ cycling. Thus, under future warmer winter conditions, increased carbon and nutrient losses from oceanic mountain ecosystems could occur if winters with little snow coincide with wet spring conditions.